MALT-1 mediates IL-17 neural signaling to regulate C. elegans behavior, immunity and longevity - Sean M. Flynn (Nature Portfolio, 2020)
IL-17 is a pro-inflammatory molecule that can also regulate neural circuit function. Here the authors use C. elegans to show that the paracaspase MALT-1 lies downstream of IL-17 signaling and regulates many aspects of C. elegans biology, including escape behavior, associative learning, immunity and longevity.